2002
DOI: 10.1242/jeb.205.7.1009
|View full text |Cite
|
Sign up to set email alerts
|

Learning speed and contextual isolation in bumblebees

Abstract: SUMMARY Bumblebees will learn to approach one of a pair of patterns (a 45°grating) and to avoid the other (a 135° grating) to reach a feeder, and to do the opposite to reach their nest (approach a 135° grating and avoid a 45° grating). These two potentially competing visuo-motor associations are insulated from each other because they are set in different contexts. We investigated what training conditions allow the two sets of associations to be acquired without mutual interference. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Similar transfer effects have also been documented in other animals, where prior experience in solving a functionally identical, but perceptually different problem, aided in selecting the right tool to solve the subsequent problem (Bobrowicz et al, 2020, 2021). The degree of transfer tends to be greater when responses are similar or when stimuli are similar (Cheng, 2005; Colborn et al, 1999; Fauria et al, 2002; Lewis et al, 2013; Roberts, 1981). Our findings regarding failed visits align with this observed pattern and with Osgood’s framework, as we observed that transfer increased more in similar stimuli – identical responses treatment than distinct stimuli – identical responses treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar transfer effects have also been documented in other animals, where prior experience in solving a functionally identical, but perceptually different problem, aided in selecting the right tool to solve the subsequent problem (Bobrowicz et al, 2020, 2021). The degree of transfer tends to be greater when responses are similar or when stimuli are similar (Cheng, 2005; Colborn et al, 1999; Fauria et al, 2002; Lewis et al, 2013; Roberts, 1981). Our findings regarding failed visits align with this observed pattern and with Osgood’s framework, as we observed that transfer increased more in similar stimuli – identical responses treatment than distinct stimuli – identical responses treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, basic similarities in the flower structure itself may have helped bees to minimize confusion in executing the appropriate motor routine. Contextual cues are known to reduce interference effects (Cheng, 2005; Colborn et al, 1999; Fauria et al, 2002; Lewis et al, 2013; Roberts, 1981), unless the contextual cues are not sufficiently learned (Fauria et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, context‐dependent learning capacity has been demonstrated for visual pattern discrimination learning (in bumblebees: Fauria et al, 2002; in ants: Chameron et al, 1998) and for learning of the position of a visual target (in cockroaches: Kwon et al, 2004). A context‐dependent form of olfactory learning that is useful for the study of underlying neural mechanisms had not been established in any insects.…”
Section: High Capability Of Learning and Memory In Cricketsmentioning
confidence: 99%